Bioinformatics reveals TNFAIP6 as a candidate gene and suggests its potential crosstalk in the treatment of hemodialysis in chronic kidney disease - Guoxin Zhang; Jieqiong Fu; Wenming Niu (Renal Failure, 2025)
Hemodialysis (HD) is a life-sustaining treatment for chronic kidney disease (CKD) patients. This study aimed to identify candidate diagnostic biomarkers associated with HD-treated CKD. The public dataset was acquired from the Gene Expression Omnibus database. The differentially expressed genes (DEGs) showing opposite trends across the three groups were obtained as crosstalk genes, and their potential pathways were explored through KEGG and GSEA analyses. Next, hub genes were identified using LASSO regression, and their diagnostic potential was assessed via ROC analysis. Key immune cell populations were identified using ssGSEA. Blood samples from healthy controls (n = 10), CKD patients (n = 9), and HD-treated CKD patients (n = 7) were collected to validate hub gene expression. A total of 132 crosstalk genes were identified, with the TGF-β and KRAS signaling pathways potentially activated in the HD group. Two hub genes, SIK1 and TNFAIP6, exhibited AUC values exceeding 0.8 for diagnosing CKD and HD-treated CKD groups. Compared to the other groups, neutrophil abundance was significantly higher in CKD group and showed a strong correlation with the hub genes. External datasets and RT-qPCR validated a consistent expression trend of TNFAIP6. Therefore, TNFAIP6 may represent a potential candidate gene with biomarker relevance in CKD and HD-treated CKD. TNFAIP6 has been previously associated with the TGF-β pathway and neutrophil regulation, and its crosstalk mechanism in HD-treated CKD warrants further exploration.